This is how you grow after trauma : simple strategies for resilience, confidence, healing & hope - Remes, Olivia (Sourcebooks, 2023)
From leading mental health expert Dr. Olivia Remes, this essential companion for navigating life's challenges offers everyday techniques and exercises to overcome setbacks and even achieve positive change. Whether you're dealing with job uncertainty, ill health, relationship problems, financial or mental health struggles, or the loss of a loved one, this highly practical and compassionate book will help you find meaning amidst the chaos and reset your life. Distilling cutting-edge science and psychology, and backing it up with examples of everyday people who have overcome the odds by harnessing their inner strength, This is How You Grow After Trauma offers a clear 5-step path toward healing from trauma and setbacks. This is your trusted, pocket-sized guide for how to turn hardship into healing and become your truest, calmest self.